Anti-Obesity Effects of Macroalgae - Gómez-Zorita, Saioa (Nutrients, 2020)
Macroalgae have attracted great interest for their potential applications in nutraceutical and pharmaceutical industries as source of bioactive medicinal products and food ingredients. This review gathers data from in vitro and in vivo studies addressing the anti-obesity effects of macroalgae. Great consensus exists in all reported in vitro studies concerning the reduction induced by seaweed extracts in the expression of transcriptional factors controlling adipogenesis. In animals, macroalgae reduced body fat accumulation and prevented other obesity features, such as dyslipidemia, insulin resistance and fatty liver. These effects are not due to food intake reduction, since few studies have reported such event. Indeed, the effects on metabolic pathways in target tissues/organs seem to play a more relevant role. Macroalgae can reduce de novo lipogenesis, limiting fatty acid availability for triglyceride synthesis in white adipose tissue. This effect has been observed in both cell cultures and adipose tissue from animals treated with macroalgae extracts. In addition, increased fatty acid oxidation and thermogenic capacity, as well as a shift towards healthier gut microbiota composition may contribute to the body fat-lowering effect of macroalgae. Studies in humans are needed to determine whether macroalgae can represent a feasible tool to prevent and/or manage overweight and obesity.